Forhandlinger ved Lolland-Falster Forstmandsforenings Møde d. 2den Oktbr. 1871. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Forhandlinger ved Lolland-Falster Forstmandsforenings Møde d. 2den Oktbr. 1871.